Fission and fusion scenarios for magnetic microswimmer clusters - Francisca Guzmán-Lastra (Nature Portfolio, 2016)
The collective motion of microswimmers is determined by not only their direct interaction, but also the hydrodynamics forces mediated by the surrounding flow field. Here, the authors detail in simulation the spontaneous assembly and disassembly of magnetic microswimmers into various structures.